Evaluating the Management Effectiveness of the Biomass Based Independent Energy Village (DME) Program in Supporting Indonesia’s Zero Carbon NDC - Muhammad Taali; Fredy Susanto; Lala Hucadinota Ainul Amri (Politeknik Siber Cerdika Internasional, 2026)
Background: Indonesia's updated Nationally Determined Contribution (NDC) targets net zero emissions by 2060, making the transition to renewable energy particularly locally based sources—essential for climate mitigation. Biomass, as a key renewable resource, is utilized through the Energy Independent Village (Desa Mandiri Energi, DME) program, including in Kaliombo Village, Jepara, which uses buffalo dung as a sustainable energy source. Objective: This study evaluates the management effectiveness of a biomass-based Energy Independent Village (DME) program in Kaliombo Village, Jepara Regency, Indonesia, and its contribution to the national zero carbon NDC target by 2060. Methods: Using a qualitative case study approach, data were collected through in-depth interviews with village officials, program managers, and community members, supplemented by observation and documentation. Data were analyzed using thematic analysis with triangulation to ensure trustworthiness. Result: Findings reveal that while the program demonstrates measurable contributions to local energy security and green energy production, long-term sustainability depends on strengthened managerial capacity, community participation, and policy alignment. Conclusion: This study provides managerial insights for improving renewable energy governance at the village level and offers a replicable framework for developing biomass-based rural energy in support of national decarbonization goals. This study contributes a replicable governance framework for biomass-based rural energy programs, advancing the discourse on decentralized renewable energy management in developing countries.